Recent advances with cyclin-dependent kinase inhibitors: therapeutic agents for breast cancer and their role in immuno-oncology. Issue 7 (3rd July 2019) - Di Sante, Gabriele; Pagé, Jessica; Jiao, Xuanmao; Nawab, Omar; Cristofanilli, Massimo; Skordalakes, Emmanuel; Pestell, Richard G
ABSTRACT: Introduction : Collaborative interactions between several diverse biological processes govern the onset and progression of breast cancer. These processes include alterations in cellular metabolism, anti-tumor immune responses, DNA damage repair, proliferation, anti-apoptotic signals, autophagy, epithelial-mesenchymal transition, components of the non-coding genome or onco-mIRs, cancer stem cells and cellular invasiveness. The last two decades have revealed that each of these processes are also directly regulated by a component of the cell cycle apparatus, cyclin D1. Area covered : The current review is provided to update recent developments in the clinical application of cyclin/CDK inhibitors to breast cancer with a focus on the anti-tumor immune response. Expert opinion : The cyclin D1 gene encodes the regulatory subunit of a proline-directed serine-threonine kinase that phosphorylates several substrates. CDKs possess phosphorylation site selectivity, with the phosphate-acceptor residue preceding a proline. Several important proteins are substrates including all three retinoblastoma proteins, NRF1, GCN5, and FOXM1. Over 280 cyclin D3/CDK6 substrates have b\een identified. Given the diversity of substrates for cyclin/CDKs, and the altered thresholds for substrate phosphorylation that occurs during the cell cycle, it is exciting that small molecular inhibitors targeting cyclin D/CDK activity have encouraging results in specific tumors.